Designing and Fabricating a Paintball Marker - Atikah, Mohd Ramli; Jamali, Md Sah; Shah Fener Khan, Mohd Khan; Zulkifli, Abdul Rashid; Mohd Hatta, Musa; Ahmad Humaizi, Hilmi (2010)
Atikah Mohd Ramli and her team were participate in IPTA R&D Expo 2005, 30th September - 2nd October 2005 at Putra World Trade Center (PWTC), Kuala Lumpur. Organized by Ministry of Higher Education (MOHE) and host by Universiti Teknologi Malaysia (UTM).